Walking together: Relational Yarning as a mechanism to ensure meaningful and ethical Indigenous oral health research in Australia - Brianna Poirier; Joanne Hedges; Lisa Jamieson (Elsevier, 2022)
Abstract Objective: Despite the colonial roots and modern presence of systemic racism within academic institutions, Indigenous researchers have successfully led a change in expectations of what constitutes 'good' research with Indigenous Communities. From a mixed Indigenous and non‐Indigenous research perspective, this paper explores the processes that enable meaningful and ethical Indigenous oral health research. Methods: This paper utilises Yarning as its methodology to capture our research process and identify our core values. The idea for this paper was a result of social and collaborative yarns, which were used as the framework for a final research topic yarn. Results: We propose Relational Yarning as a mechanism to ensure the prioritisation of six core values in our research approach: respect, relationships, advocacy, reciprocity, time and gratitude. Conclusions: We argue that these values are not only essential at the individual or team level but must extend to all institutions in which Indigenous research operates. Therefore, academic institutions, funding bodies and academic journals are compelled to mandate policies that disrupt patterns of symbolic violence and eliminate institutional racism. Implications for public health: Our framework provides an opportunity for all researchers engaging with Indigenous Communities to facilitate meaningful and ethical research and prioritise culturally secure research environments.